Removal of minocycline from wastewater via Co/Zn-MOFs -derived porous carbon materials as adsorbents - Fuhua Wei; Peng Chen; Qinhui Ren; Qin Zhang; Wei Shang; Diaodiao Zhang; Min Li; Zhao Liang (Results in Chemistry)
The Co/Zn-MOFs material was synthesized successfully via the solvothermal method and then underwent calcination at 900 °C. To investigate its structural properties, multiple characterization techniques were applied, such as scanning electron microscopy (SEM), Fourier-transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), and nitrogen adsorption-desorption isotherms. These analyses aimed to assess the features of the carbon material for its efficacy in minocycline removal. The experimental findings demonstrated that the ideal conditions for maximizing minocycline adsorption on the carbon material obtained from Co/Zn-MOFs comprised a dosage of 20 mg, a solution concentration of 50 ppm, and a pH level of 10. Furthermore, kinetic studies revealed that the pseudo-second-order model accurately represented the experimental data. In conclusion, this research underscores the remarkable adsorption capability of the carbon material derived from Co/Zn-MOFs for minocycline, indicating potential applications in environmental cleanup and presenting an innovative approach for environmental preservation.